Perbedaan Tingkat Stres Antara Guru Sekolah Luar Biasa Di SLB Negeri Surakarta Dengan Guru Reguler Di SMP Negeri 1 Surakarta - Mustikarini, Ayu; , dr. Wahyu Nur Ambarwati, Sp.Kj; , dr. Budi Hernawan (2016)
Background: Problem which emerge at regularry teacher it is of course differ from the problem at special education teacher or extraordinary school. Extraordinary School teacher have the compared to higher stress level than regularry teacher. This matter was caused a child have special requirement to require the more attention and training compared a normal child so that to handle it can generate the physical fatigue and bounce remarkable. Objective: Knowing there was difference stress level between extraordinary school teacher in State Owned Extraordinary School of Surakarta with the Regularry Teacher in 1 State-Owned Junior High School of Surakarta. Method: The study used observational analytic with cross sectional approach. Research subject was extraordinary school teacher and regularry teacher which get away L-Mmpi test and have worked to minimize one year in school taken by purposive sampling so that obtained sample equal to 34 teacher consisted by 17 extraordinary teacher and 17 regularry schoolteacher. Data analyze was using independent sample t test. Result: Based on independent sample t-test was known the mean stress level extraordinary school teacher of Surakarta equal to 0,8680 while the stress level the 1 stated owned junior high school of Surakarta equal to 0,5452, obtained p value = 0,000 ( p<0,05) so that interpreted that there were difference significance between extraordinary school teacher with the regularry teacher. Extraordinary shchool teacher stress level higher than stress level of regularry teacher. Conclusion: There wewe difference significant extraordinary school teacher of Surakarta stress level of with 1 stated owned junior high school of Surakarta stress level.